Negotiating the dual religiosity of African Indigenous Religion and Christianity among Bemba Catholics - Armstrong Chanda; Austin Mumba Cheyeka; Tomaida L. C Milingo (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2026)
The practice of dual religiosity of Christianity and Indigenous African Religion (AIR), among Bemba Catholics in the Muchinga Province of Zambia, is a lived reality. Bemba Catholics exist in a region where two different worldviews exist, which leads them to practise their faith through a combination of different beliefs and practices while encountering difficulties when their Christian faith faces challenges from their indigenous practices and cultural traditions. Therefore, the study examines how this dual religiosity is negotiated. The study used a hermeneutic phenomenological approach to study 20 Bemba Catholics who formed the sample size from Chilonga and Ilondola. Bemba Catholics blend AIR elements with Catholicism through integration, syncretism, adaptation, contextualisation and juxtapositioning. They create new rituals that combine both traditions, selectively adopting AIR beliefs, interpreting them through a Christian lens, and maintaining their Christian identity. They establish their Catholic identity by practicing Catholicism through their traditional African rituals. Some maintain clear boundaries, whereas others embrace hybridity. These strategies show that religious negotiation has changed throughout history, while participating in dual religiosity and cultural identity, and maintaining indigenous beliefs under Christian influence results in insufficient support by religious organisations and limits interfaith dialogue opportunities.